Analysis of the relationship between different intensities of physical activity and pulse wave velocity in adults: an epidemiological study - De Moraes-Ferrari, G (MOSBY-ELSEVIER, 2026)
Background: Arterial stiffness, reflected by pulse wave velocity (PWV), is an important cardiovascular risk marker. Physical activity (PA) may reduce arterial stiffness, but the most beneficial intensity remains unclear. The objective this study was to analyze the relationship between different intensities of PA and arterial stiffness in adults and to verify whether these relationships are independent of sex, age, and socioeconomic status. Methods: A total of 185 participants (104 women) were included in this study. Arterial stiffness was assessed using PWV, measured by a non-invasive oscillometric device (Arteriograph AOP). Three consecutive measurements were performed (with one-minute intervals), and the device provided the final PWV value. PA intensity (light, moderate, and vigorous) was objectively measured using an ActiGraph GT3X accelerometer. The associations between PWV and PA intensities were examined using Pearson s correlation and linear regression models, with the crude model and subsequently adding sex, age, and socioeconomic status, to estimate the magnitude of these associations. Results: An inverse relationship was found between PWV and vigorous-intensity PA in the unadjusted model ((3 = -0.007; 95 % CI: -0.011, -0.002; p = 0.006). This association remained significant after adjustment for sex ((3 = -0.006; 95 % CI: -0.010, -0.001; p = 0.010), but lost significance after additional adjustment for age ((3 = -0.001; 95 % CI: -0.004, 0.001; p = 0.323). No associations were observed between PWV and light or moderate PA. Conclusion: PWV was inversely associated with vigorous-intensity PA; however, but age appears to exert a strong influence on this relationship.